Unsung valor : a GI's story of World War II - Harrison, A. Cleveland (University Press of Mississippi, 2003)
Thirty riveting months in the life of a common infantryman, one among the "citizen soldiers" who took the Allies to victory When drafted into the army in 1943, A. Cleveland Harrison was a reluctant eighteen-year-old Arkansas student sure that he would not make a good soldier. But inside thirty months he manfully bore arms and more. This book is his memoir about becoming a soldier, a common infantryman among the ranks of those who truly won the war. After the Allied victory in 1945, books by and about the major statesmen, generals, and heroes of World War II appeared regularly. Yet millions of